The model of the formation of the individual's spiritual intelligence in the context of the processes of radicalization of modern youth - Zelenkov, Mikhail Yuryevich (2021)
The purpose of the article is to identify and build a mental model of the formation of the spiritual intelligence of a young individual. The research methodology was a humanistic approach, which made it possible to pay priority attention to the problems of a young individual, his/her search for the meaning of life and the determination of value orientations, as well as the process of modernizing the directions of society's activities and the development of new approaches to the formation of the spiritual intelligence of a young person. The main results of the study were: the identification of relevant factors in the 21st century, the consequences of the negative impact on the spiritual intelligence of an individual with an immature worldview system lead him/her to enter the path of radicalization; the creation of a mental model that reveals the dependence of the transformation of the spiritual intelligence of a young individual, and, consequently, the vector of his/her behaviorism from the influence of external and internal factors, as well as the construction of a mathematical model describing the process of its functioning. The results obtained in the course of the study will provide significant assistance to state authorities and law enforcement agencies in preventing the radicalization of young people in the modern world and will allow building a system of youth policy that is adequate to a democratic society.